PENGGUNAAN METODE MIND MAPPING DALAM MENINGKATKAN KEAKTIFAN BELAJAR SISWA PADA PEMBELAJARAN FIKIH KELAS VIII C DI MADRASAH TSANAWIYAH NEGERI 1 KOTA JAMBI - Fathul Mudtadiah, Siti; Syahbani, Nispi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aimed to improve students’ learning activeness through the use of the mind mapping method in Fiqh learning for Grade VIII C at Madrasah Tsanawiyah Negeri 1 Kota Jambi. The research employed Classroom Action Research conducted in two cycles consisting of planning, action, observation, and reflection stages. The participants of this study were students of class VIII C. Data were collected through classroom observation, student learning activeness questionnaires, and interviews, and were analyzed using descriptive quantitative techniques in the form of percentages. The findings revealed that the implementation of the mind mapping method was effective in increasing students’ learning activeness. In Cycle I, students’ activeness reached 65.8% and was categorized as active, while in Cycle II it increased to 84.2% and was categorized as very active, showing an improvement of approximately 18.4%. Questionnaire and interview results also indicated positive responses from the students toward the learning activities. The improvement in learning activeness was reflected in students’ involvement during lessons, participation in discussions, willingness to ask and answer questions, ability to explore information, engagement in collaborative work, completion of practice activities, and application of learning materials to daily life situations. Therefore, the mind mapping method can be concluded to be an effective instructional strategy for enhancing students’ learning activeness in Fiqh learning for Grade VIII C at Madrasah Tsanawiyah Negeri 1 Kota Jambi.